Successfully treated HHV-6 encephalitis in a patient without immunocompromised conditions - Maeda, Tetsuya; Suzuki, Yoshio; Terayama, Yasuo; Iwaoka, Kazuhiro (Journal of Iwate Medical Assiociation, 2019)
Human herpesvirus 6 (HHV-6) is known to cause encephalitis and meningitis in immunosuppressed humans, but there have been on few reports in patients without immunodeficiency. We reported a successfully treated 73-year-old man involved with acute HHV-6 encephalitis, who had no underlying disease or history of medication that might induce immunodeficiency. He initially showed disturbance of consciousness and memory impairment and these symptoms were rapidly deteriorated without any neuroradiological findings. The patient was initially diagnosed with herpes zoster-related encephalitis and received treatment with acyclovir, because he had a history of herpes zoster prior to his symptoms. His progressive disturbance of consciousness was dramatically improved by adjunctive steroid pulse therapy. HHV-6 was detected in cerebrospinal fluid, and other virus DNAs and markers were not detected in cerebrospinal fluid and blood. Thus, the patient was finally diagnosed with HHV-6 encephalitis.